2013
DOI: 10.1103/physrevd.87.127501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eccentricity on binary neutron star searches in advanced LIGO

Abstract: Binary neutron stars (BNSs) are the primary source of gravitational waves for the Laser Interferometer Gravitational-wave Observatory (LIGO) and its international partners Virgo and KAGRA. Current BNS searches target field binaries whose orbits will have circularized by radiation reaction before their gravitational waves enter the Advanced LIGO sensitive band at 15 Hz. It has been suggested that a population of BNSs may form by n-body interactions near supermassive black holes or in globular clusters and that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
94
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 47 publications
(68 reference statements)
7
94
0
Order By: Relevance
“…These studies have shown that detecting and characterizing eccentric binary systems will not be feasible using existing algorithms for quasicircular binaries [33,72]. Furthermore, as discussed in Ref.…”
Section: Introductionmentioning
confidence: 98%
“…These studies have shown that detecting and characterizing eccentric binary systems will not be feasible using existing algorithms for quasicircular binaries [33,72]. Furthermore, as discussed in Ref.…”
Section: Introductionmentioning
confidence: 98%
“…Huerta and Brown estimate signal-to-noise ratio loss factors of about 0.5 and 0.2 for BNS systems with eccentricities of 0.2 and 0.4 respectively [11]. This would bring the matched filtering sensitivity distances of these signals to 225 Mpc and 90 Mpc, compared to 160 Mpc for these two eccentricity values when using seedless clustering; therefore seedless clustering with eccentric template banks may provide further opportunities for observing these types of signals.…”
Section: Discussionmentioning
confidence: 99%
“…Up until now, there have been no dedicated matched filtering searches for low a Electronic address: coughlin@physics.harvard.edu b Electronic address: meyers@physics.umn.edu mass binaries with low to moderate eccentricities. Huerta and Brown have shown that searches using waveforms that assume no eccentricity are significantly sub-optimal above > 0.05 [11]. They conclude that in order to detect and study the rate of eccentric stellar-mass compact binaries in aLIGO, a search specifically targeting these systems will need to be constructed.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately gravitational wave observations will be the primary tool to measure eccentricity of compact object inspirals and to constrain the rate of eccentric compact mergers. Unfortunately, the present detection template bank used by LIGO is entirely circular [5,52], hindering detection of systems with in-band eccentricities above about e ∼ 0.1 [25,53,54]. Due to this same absence of eccentric waveform models, parameter estimation must likewise assume quasi-circularity.…”
Section: Introductionmentioning
confidence: 99%